Application of Finger Painting Techniques to Develop Drawing Creativity in Children Aged 4-5 Years (Universitas Pendidikan Indonesia Kampus Cibiru, 2025)
This research is motivated by the low creativity of early childhood children at RA At-Taufiq, Cikalongkulon District, where their artworks still tend to be similar, so that more varied and enjoyable learning methods are needed. The purpose of this study is to describe the application of finger painting techniques in developing the artistic creativity of children aged 4-5 years and to identify inhibiting factors and the solutions taken. The research uses a qualitative approach with a case study type, through observation, interview, and documentation techniques, and is analyzed through the stages of data reduction, presentation, and drawing conclusions. The results show that finger painting activities contribute significantly to increasing children's creativity, marked by their ability to express ideas freely, demonstrate fluency, flexibility, originality, and elaboration in their work, as well as increasing fine motor skills and courage to express themselves. This is because finger painting not only develops the artistic aspect, but also has emotional and psychological benefits, because it can be calming, increase self-confidence, and help children channel expression and creativity freely. This technique can also be linked to three theories of creativity that underlie the approach in the study of early childhood development. Thus, finger painting has proven to be effective as a holistic, fun, and meaningful learning method in fostering creativity in early childhood.